Virtual Reality-Induced Sensorimotor Conflict Evokes Limb-Specific Sensory Disturbances in Complex Regional Pain Syndrome - Brun, Clémentine; Pinard, Anne Marie; McCabe, Candida S.; Mercier, Catherine (Frontiers in Virtual Reality, 2021)
The origin of sensory disturbances in complex regional pain syndrome (CRPS) remains unclear. It has been hypothesized that such disturbances are due to attentional effects and/or sensorimotor integration deficits. If sensory disturbances are explained by sensorimotor integration deficits, they would be expected to be specific in terms of the category of sensation evoked and in terms of localization. Objective 1: To test whether sensory disturbances evoked by a unilateral sensorimotor conflict are specific to the painful limb and differ according to the category of sensory disturbances in individuals with a unilateral CRPS compared to healthy controls (HC). Objective 2: To assess the association between clinical characteristics and conflict-induced sensory disturbances. Objective 3: To assess conflict-induced motor disturbances. Ten adults with upper limb (UL) CRPS and 23 HC were recruited. Sensorimotor conflict was elicited with a KINARM exoskeleton interfaced with a 2D virtual environment allowing the projection of a virtual UL that was moving in either a congruent or incongruent manner relative to the actual UL movement. Participants rated sensory disturbances from 0 (no change) to 3 (high change) on a 8-item questionnaire. Items were classified into two Categories (Category 1: pain, discomfort, the feeling of losing a limb, change in weight and temperature; Category 2: feelings of peculiarity, the impression of gaining a limb and losing control). Motor disturbances were quantified as mediolateral drift and changes in amplitude of UL movement. Clinical characteristics included the intensity and duration of pain, proprioception, and body perception. CRPS participants report higher Category 1 than Category 2 disturbances for the Affected limb (while the reverse was observed for HC and for the Unaffected limb). In addition, no difference was observed between the Unaffected limb in CRPS and the Dominant limb in HC for Category 2 disturbances, while higher conflict sensitivity was observed for Category 1 disturbances. Conflict sensitivity was only related to higher pain for Category 1 disturbances in the Affected limb. Finally, no effect on motor disturbances was observed. While they do not completely rule out the attentional hypothesis, these results support the hypothesis of sensorimotor integration deficits.